1992
DOI: 10.1055/s-2007-1000311
|View full text |Cite
|
Sign up to set email alerts
|

Klinischer Vergleich verschiedener Infusionsregime im Rahmen der postoperativen On-demand-Analgesie mit Fentanyl

Abstract: 80 patients (ASA I-III, mean age 40-50 years, mean weight 59-68 kg) recovering from major gynaecological surgery (170-200 min) under balanced anaesthesia were randomly assigned to four groups to self-administer intravenous fentanyl during the early postoperative period. PCA devices were ODAC and Prominject with fentanyl demand doses of 34.5 or 34 micrograms, respectively, and lockout times of 1 or 5 min. Concurrent fentanyl infusion was none (group Prom), fixed-rate with 4 micrograms/h (group ODACf), tail-dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…[37][38][39][40][41][42][43] Tamsen's Prominject was the first device to adjust background infusion rates according to the frequency of earlier demands, but clinical efficacy could not significantly be enhanced. 44 This concept has recently caused new interest with the introduction of "rapidly learning" PCA devices, taking into account demand history and electronically registered pain scores. 45 Shieh et al demonstrated for 25 extracorporeal shock-wave lithotripsy patients that a fuzzy logic PCA algorithm with alfentanil improved pain relief during conscious sedation and reduced opioid consumption.…”
Section: New Devices and Application Strategiesmentioning
confidence: 99%
“…[37][38][39][40][41][42][43] Tamsen's Prominject was the first device to adjust background infusion rates according to the frequency of earlier demands, but clinical efficacy could not significantly be enhanced. 44 This concept has recently caused new interest with the introduction of "rapidly learning" PCA devices, taking into account demand history and electronically registered pain scores. 45 Shieh et al demonstrated for 25 extracorporeal shock-wave lithotripsy patients that a fuzzy logic PCA algorithm with alfentanil improved pain relief during conscious sedation and reduced opioid consumption.…”
Section: New Devices and Application Strategiesmentioning
confidence: 99%